Electrical and structural studies of polymer electrolyte based on chitosan/methyl cellulose blend doped with BMIMTFSI - Misenan, MSM; Isa, MIN; Khiar, ASA (Iop Publishing Ltd, 2024)
Indexed by WOS/ Scopus